Kedudukan dan Fungsi Camat Sebagai Penghubung Pemerintahan Kabupaten dengan Pemerintahan Desa Menurut Peraturan Pemerintah Nomor 17 Tahun 2018” Tentang Kecamatan : (Studi di Kecamatan Hawu Mehara Kabupaten Sabu Raijua) - Karel Nedo; Herinimus Ratu Udju; Cyrilius W. T Lamataro (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
This study analyzes the position and function of the sub-district as a liaison between the district and the village government according to government regulation No. 17 of 2018 concerning sub-districts in Hawu sub-district, Sabu Raijua district. The method used in this study is the empirical judiciary method using primary data and secondary data. The administration of the government of the Unitary State of the Republic of Indonesia is divided into provincial areas and the provincial area is divided into districts and cities, where each province, district and city has a regional government, which is regulated by law. The implementation of local government in the sub-district has undergone a change in status, which was initially an administrative area, now it is the work area of the sub-district as a district apparatus in terms of public services. A series of other changes also occurred, such as in the main duties and authorities in the sub-district. The formulation of the problem in this study is: (1) What is the position and function of the sub-district head in the sub-district government according to Government Regulation Number 17 of 2018?, and (2) What are the factors that affect the sub-district head in carrying out its duties, and its functions according to Government Regulation Number 17 of 2018?. From the results of the research, the researcher can conclude that the position of the sub-district and sub-district in coordinating the relationship between the district government and the village government according to government regulation Number 17 of 2018. The position of the sub-district is no longer a unit of government power, but as a unit of work or service area and the inhibiting factor that can affect the function and duties of the sub-district head lies in the human factor, this human factor is divided into several elements including the sub-district, village head and community leaders among the three elements there is only one element that provides an inhibited influence on the duties and functions of the sub-district, These elements are the elements of the village head, the existence of village heads whose technological capabilities are lacking or what is commonly called technological stuttering (Gaptek) resulting in inhibition of communication through online considering that technology is now increasingly sophisticated, so the use of technology is indeed highly recommended to facilitate online communication between the sub-district head and the village head.